Selection principles of plant korne formation stimulators among bacteria Pseudomonas with antagonistic activity - Kuleshova, Yuliya M.; Rybakova, Viktoria A.; Feklistova, Irina N.; Grineva, Irina A.; Lomonosova, Veronica A.; Skakun, Tatyana L.; Maslak, Diana V.; Sadovskaya, Ludmila E.; Maximova, Natalia P. (Experimental Biology and Biotechnology, 2018)
Among the PGPR Pseudomonas with antagonistic activity from «fluorescent» group, strains capable of improving the mineral nutrition of plants have been identified. The influence on plant growth processes and the phytopathogenic factors of studied bacteria are estimated. When analyzing the growth-stimulating activity of preparations on the basis of 14 different bacterial cultures, a reliable increase in the root length was registered, up to 90 %, shoots – up to 95 %, seed germination – up to 30 % relative to control. Thus, non-pathogenic fluorescent Pseudomonas can be antagonists of phytopathogens, improve soil mineralization and stimulate root formation of plants simultaneously, which leads to an increase in the plant productivity.